2018
DOI: 10.1111/pce.13133
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of photosynthetic heat tolerance in plants adapted to thermally contrasting biomes

Abstract: In many biomes, plants are subject to heatwaves, potentially causing irreversible damage to the photosynthetic apparatus. Field surveys have documented global, temperature-dependent patterns in photosynthetic heat tolerance (P ); however, it remains unclear if these patterns reflect acclimation in P or inherent differences among species adapted to contrasting habitats. To address these unknowns, we quantified seasonal variations in T (high temperature where minimal chlorophyll-a fluorescence rises rapidly, ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
153
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(177 citation statements)
references
References 73 publications
(123 reference statements)
23
153
1
Order By: Relevance
“…The increase in thermal tolerance reported here (~0.25°C per 1.0°C change in average leaf temperature; Figure b) is broadly consistent with the seasonal change reported by O'Sullivan et al. () and Zhu et al (), confirming that acclimation of leaf thermal tolerance mitigates some of the risk associated with future heatwaves. Possible limits to the adjustment of leaf thermal tolerance remain a key unknown for future research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in thermal tolerance reported here (~0.25°C per 1.0°C change in average leaf temperature; Figure b) is broadly consistent with the seasonal change reported by O'Sullivan et al. () and Zhu et al (), confirming that acclimation of leaf thermal tolerance mitigates some of the risk associated with future heatwaves. Possible limits to the adjustment of leaf thermal tolerance remain a key unknown for future research.…”
Section: Discussionsupporting
confidence: 91%
“…They also demonstrated acclimation in leaf thermal tolerance of ~0.3°C per 1.0°C increase in growth temperature using repeated measurements of six species in contrasting warm and cool seasons. This observation has been subsequently confirmed for 62 species across Australia (Zhu et al., ). O'Sullivan et al.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have found that trees can acclimate to warmer temperatures and heatwaves by increasing the high temperature threshold for leaf photosynthetic and respiratory function (Drake et al, ; Knight & Ackerly, ; Zhu et al, ). We also tested whether species acclimate to heatwave conditions by increasing T max and reducing basal respiration rates.…”
Section: Discussionmentioning
confidence: 99%
“…Even when high temperatures reduce A , some tree species maintain high g s (and transpiration) which helps cool leaves (Drake et al, ; Urban, Ingwers, McGuire, & Teskey, ). There is also evidence that trees can tolerate temperatures much higher than they typically experience (O'Sullivan et al, ) and may acclimate to high temperatures by increasing the thermal limits of leaf function (e.g., photosynthesis, respiration; Drake et al, ; Sastry & Barua, ; Zhu et al, ). Isoprene and HSPs may facilitate acclimation to high temperatures; yet, associations between I s , HSP production, and changes in the thermal limits of leaf function in response to heatwave conditions have not been tested.…”
Section: Introductionmentioning
confidence: 99%
“…However, in summer sunny conditions, leaves can heat up to even higher temperatures of 45–55 °C (Valladares & Niinemets, ), especially the leaves in large‐leaved species in conditions of soil water stress, where stomatal closure leads to reduced latent heat loss via transpiration (Gutschick, ; Michaletz et al, ; Wright et al, ). Such extreme temperatures typically result in irreversible reductions in leaf photosynthetic activity, implying that these high temperatures constitute a stress to the leaves (Zhu et al, in this issue). Global change is predicted to lead to an overall increase in ambient temperature and greater frequency of heat waves and enhanced severity of drought in many parts of the world (Deryng, Conway, Ramankutty, Price, & Warren, ; Field et al ), implying that global plant productivity could be more severely suppressed by elevated temperatures and heat stress in future climates.…”
Section: Introductionmentioning
confidence: 99%